Faktor Kejadian Diare Pada Balita - Arief Fardiansyah (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2020)
Children under five years of age was a period of growth and development of children who need special attention from parents especially mothers,because age is prone to nutrition and prone to infectious diseases.Diarrhea dominant attacking under five years of age because the endurance of the their body is still weak so very so that they are susceptible to the spread of bacteria that cause diarrhea.Design research was descriptive.Population all mothers who have children and have diarrhea taken with concecutive sampling as many as 65 respondents.The results showed that most mothers of children under five years of age who had diarrhea had a high school education (60%),had family-income according to standart of city minimum age (46.4%), did not have a job or as a housewife (44.6%) And did not provide exclusive breast milk (53.8%).Analyzed by frequency distribution.Work,education and income are factors that influence the behavior of mothers in preventing diarrhea in children under five years of age.Exclusive breast feeding can increase immunity in children under five years.Therefore, mothers should be able to improve the information diarrhea either by following the counseling of health workers or through reading magazines so that it can increase the knowledge in prevention of diarrhea in children.